The management of cardiac implantable electronic device lead perforations: a multicentre study. Issue 6 (26th April 2019) - Rav Acha, Moshe; Rafael, Allon; Keaney, John J; Elitzur, Yair; Danon, Asaf; Shauer, Ayelet; Taha, Louay; Shechter, Yonat; Bogot, Naama R; Luria, David; Ilan, Michael; Singh, Sheldon M; et al.
Abstract: Aims: Lead perforation is a rare, well-known complication of cardiac implantable electronic device (CIED) implants, whose management is mostly not evidence-based. Main management strategies include conservative approach based on clinical and lead function follow-up vs. routine invasive lead revision approach. This study compared the complications of both strategies by composite endpoint, including recurrent perforation-related symptoms, recurrent pericardial effusion (PEf), lead dysfunction, and device infection during 12 month follow-up. Methods and results: Multicentre retrospective analysis, inquiring data from imaging studies, device interrogation, pericardiocentesis, and clinical charts of patients with suspected perforating leads between 2007 and 2014 in five hospitals. All cases were reviewed by electrophysiologist and defined as definite perforations by suggestive symptoms along with lead perforation on imaging, bloody PEf on pericardiocentesis shortly after implant, or right ventricular (RV) lead non-capture along with diaphragmatic stimulation upon bipolar pacing. Clinical outcomes associated with both management approaches were compared, with respect to the composite endpoint. The study included 48 definitive perforation cases: 22 managed conservatively and 26 via lead revision. Conservative management was associated with an increased composite endpoint compared with lead revision (8/22 vs. 1/26; P  = 0.007). The dominant complication among the conservative cohort was appearance of cardiac tamponade during follow-up; 5/6 occurring in cases which presented with no or only mild PEf and were treated by antiplatelets/coagulants during or shortly after CIED implantation. Conclusion: A conservative management of CIED lead perforation is associated with increased complications compared with early lead revision. Lead revision may be the preferred management particularly in patients receiving antiplatelets/coagulants.